Vi4-miR-185-5p-Igfbp3 Network Protects the Brain From Neonatal Hypoxic Ischemic Injury via Promoting Neuron Survival and Suppressing the Cell Apoptosis - Xiong, Liu-Lin; Xue, Lu-Lu; Du, Ruo-Lan; Zhou, Hao-Li; Tan, Ya-Xin; Ma, Zheng; Jin, Yuan; Zhang, Zi-Bin; Xu, Yang; Hu, Qiao; Bobrovskaya, Larisa; Zhou, Xin-Fu; et al. (Frontiers in Cell and Developmental Biology, 2020)
Neonatal hypoxic ischemic encephalopathy (HIE) due to birth asphyxia is common and causes severe neurological deficits, without any effective therapies currently available. Neuronal death is an important driving factors of neurological disorders after HIE, but the regulatory mechanisms are still uncertain. Long non-coding RNA (lncRNA) or ceRNA network act as a significant regulator in neuroregeneration and neuronal apoptosis, thus owning a great potential as therapeutic targets in HIE. Here, we found a new lncRNA, is the most functional in targeting the Igfbp3 gene in HIE, which enriched in the cell growth and cell apoptosis processes. In addition, luciferase reporter assay showed competitive regulatory binding sites to the target gene Igfbp3 between TCONS00044054 (Vi4) and miR-185-5p. The change in blood miR-185-5p and Igfbp3 expression is further confirmed in patients with brain ischemia. Moreover, Vi4 overexpression and miR-185-5p knock-out promote the neuron survival and neurite growth, and suppress the cell apoptosis, then further improve the motor and cognitive deficits in rats with HIE, while Igfbp3 interfering got the opposite results. Together, Vi4-miR-185-5p-Igfbp3 regulatory network plays an important role in neuron survival and cell apoptosis and further promote the neuro-functional recovery from HIE, therefore is a likely a drug target for HIE therapy.